Enhancing eCTD Submissions through Blockchain Technology: A Perspective on Security, Transparency and Efficiency - Kumar, Sushil; Komal; Narang, Raj Kumar; Singh, Amandeep (Applied Drug Research, Clinical Trials and Regulatory Affairs, 2025)
The Electronic Common Technical Document (eCTD) has streamlined regulatory submissions by offering a standardized format that improves communication and reduces errors. However, challenges such as maintaining compliance, ensuring data security, and managing complex lifecycle updates remain. This paper explores the integration of blockchain technology into eCTD submissions as a solution to these issues. Blockchain’s decentralized and immutable structure enhances data integrity, transparency, and tamper resistance. Smart contracts can automate compliance checks, reduce manual intervention, and improve process efficiency. Additionally, combining blockchain with technologies like artificial intelligence and cloud computing enables real-time data sharing, predictive analytics, and enhanced decision-making. These innovations can lead to faster regulatory reviews and improved stakeholder trust. For successful adoption, blockchain must be harmonized with existing regulatory systems through interoperable platforms and collaborative efforts among regulatory bodies, pharmaceutical companies, and technology providers. This paper highlights how blockchain can transform eCTD submissions by increasing operational efficiency, enhancing data security, and fostering transparent, streamlined regulatory processes.
Keywords: data security